1998
DOI: 10.1111/j.1471-0528.1998.tb09947.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated haemoglobin and hypertension arising in pregnancy

Abstract: We analysed a database of glycosylated haemoglobin (HbA1) in nondiabetic pregnant women to investigate the relation between glucose metabolism in the first and second trimesters and hypertensive complications of pregnancy. From a total of 1334 women, 13 had pre‐existing hypertension, 225 developed gestational hypertension and 51 developed pre‐eclampsia. At 28 weeks of gestation, the women who susequently developed gestational hypertension had a significantly higher mean HbAl than those who remained normotensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Our results suggest that GH and PE could represent different expressions of a spectrum of pathophysiological processes. Interestingly, previous work supported the hypothesis that GH, rather than PE, was associated with insulin resistance (Caruso et al 1999;Roberts et al 1998). Furthermore, we (Forest et al 2005) and others (Pouta et al 2004) have previously observed that differences in fasting insulin concentrations between women with a past history of HDP and those with normal pregnancy were mostly due to a 10-15% higher insulin concentration in those with prior GH compared with PE.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our results suggest that GH and PE could represent different expressions of a spectrum of pathophysiological processes. Interestingly, previous work supported the hypothesis that GH, rather than PE, was associated with insulin resistance (Caruso et al 1999;Roberts et al 1998). Furthermore, we (Forest et al 2005) and others (Pouta et al 2004) have previously observed that differences in fasting insulin concentrations between women with a past history of HDP and those with normal pregnancy were mostly due to a 10-15% higher insulin concentration in those with prior GH compared with PE.…”
Section: Discussionsupporting
confidence: 61%
“…Triglycerides (TG), free fatty acids (FFA) and low-density lipoprotein cholesterol (LDL-C) concentrations, especially small dense LDL-C, are increased in the presence of HDP, whereas the high-density lipoprotein cholesterol (HDL-C) concentration is decreased (Seely and Solomon 2003). HDP (Chappell et al 2002;Dekker and Sibai 1998;Roberts 2000;Roberts and Cooper 2001;Seely and Solomon 2003;Solomon and Seely 2001), and GH in particular (Caruso et al 1999;Roberts et al 1998), have been shown to be associated with insulin resistance, and women who never developed HDP during pregnancy are at lower risk of CVD (Roberts 2000;Williams 2003;Wilson et al 2003). Thus, HDP may constitute a first sign of increased CVD risk later in life, possibly through a predisposition to develop the metabolic syndrome that encompasses hypertension, lipid profile alterations, insulin resistance and abdominal obesity (Forest et al 2005;Pouta et al 2004;Williams 2003).…”
Section: Introductionmentioning
confidence: 99%
“…35 In a subgroup analysis, we observed significantly higher postload glucose levels in women who developed gestational hypertension, whereas women who developed preeclampsia had intermediate glucose levels not significantly different from those of women who remained normotensive. Consistent with these results, Roberts et al 42 reported that early pregnancy levels of hemoglobin A1c were predictive of gestational hypertension but not preeclampsia. In addition, the Toronto Tri-Hospital study of 3637 women without gestational diabetes showed a direct relation between degree of carbohydrate intolerance as measured by glucose levels after oral glucose administration and risk for preeclampsia.…”
Section: Glucose and Insulinmentioning
confidence: 56%
“…12 However, data in favor of this hypothesis are limited and conflicting. For example, some studies report an association between insulin resistance and gestational hypertension but not preeclampsia, [13][14][15][16] whereas others report the opposite. [17][18][19] Still others suggest that insulin resistance contributes to both disorders.…”
Section: Discussionmentioning
confidence: 99%
“…9 -11 Although data support a role for insulin resistance in preeclampsia, 12 evidence in gestational hypertension is conflicting and comes mostly from small, cross-sectional or retrospective case-control studies. [13][14][15][16][17][18][19][20][21][22] Furthermore, although prospective data suggest increased inflammation is associated with the development of preeclampsia, no studies have examined the role of inflammation in the pathogenesis of gestational hypertension.An increased level of C-reactive protein (CRP) is a sensitive marker of systemic inflammation that is associated with cardiovascular disease 23 and preeclampsia. 10 Sex hormone-binding globulin (SHBG) is a glycoprotein synthesized by the liver that serves as a carrier protein for circulating estrogen and testosterone.…”
mentioning
confidence: 99%